Mapping Agrochemical Properties of Typical Irrigated Serozem and Newly Irrigated Serozem-Meadow Soils of Jizzakh Region Using GIS Technologies - Normatov Yodgor Mamanazarovich; Baxodirov Zafar Abduvalievich; Tursunov Shodmon Togʼaevich (American Journal of Biology and Natural Sciences, 2025)
This article presents data on mapping the humus, nitrogen, and phosphorus content of typical irrigated gray and newly irrigated gray-meadow soils distributed in the Jizzakh region using GIS systems and technologies. Thematic maps of the distribution of humus and nutrients in irrigated soils have been developed.